The inhibition of eIF5A hypusination by GC7, a preconditioning protocol to prevent brain death‐induced renal injuries in a preclinical porcine kidney transplantation model. Issue 12 (12th June 2020) - Giraud, Sebastien; Kerforne, Thomas; Zely, Jeremy; Ameteau, Virginie; Couturier, Pierre; Tauc, Michel; Hauet, Thierry
Abstract : The eIF5A hypusination inhibitor GC7 (N1‐guanyl‐1, 7‐diaminoheptane) was shown to protect from ischemic injuries. We hypothesized that GC7 could be useful for preconditioning kidneys from donors before transplantation. Using a preclinical porcine brain death (BD) donation model, we carried out in vivo evaluation of GC7 pretreatment (3 mg/kg iv, 5 minutes after BD) at the beginning of the 4h‐donor management, after which kidneys were collected and cold‐stored (18h in University of Wisconsin solution) and 1 was allotransplanted. Groups were defined as following (n = 6 per group): healthy (CTL), untreated BD (Vehicle), and GC7‐treated BD (Vehicle + GC7). At the end of 4h‐management, GC7 treatment decreased BD‐induced markers, as radical oxygen species markers. In addition, GC7 increased expression of mitochondrial protective peroxisome proliferator‐activated receptor‐gamma coactivator‐1‐alpha (PGC1α) and antioxidant proteins (superoxyde‐dismutase‐2, heme oxygenase‐1, nuclear factor [erythroid‐derived 2]‐like 2 [NRF2], and sirtuins). At the end of cold storage, GC7 treatment induced an increase of NRF2 and PGC1α mRNA and a better mitochondrial integrity/homeostasis with a decrease of dynamin‐ related protein‐1 activation and increase of mitofusin‐2. Moreover, GC7 treatment significantly improved kidney outcome during 90 days follow‐up after transplantation (fewer creatininemia and fibrosis). Overall, GC7 treatment was shown to be protective for kidneys against BD‐induced injuries during donor management and subsequently appeared to preserve antioxidant defenses and mitochondria homeostasis; these protective effects being accompanied by a better transplantation outcome. Abstract : In a porcine kidney transplant model, treatment with an intravenous bolus of a polyamine analog initiated shortly after brain death improved not only antioxidant, mitochondrial, and cellular protective pathways prior to transplantation but also kidney function after transplantation. Schnieke et al.'s editorial is on page 3275 .